(untitled) (Research, Society and Development, 2021)
Introduction: Children with special health needs usually have physical, mental, intellectual or sensory limitations that demand from their caregivers a daily follow-up full of attention, specific care and technical and human skills. The care provided in a holistic and integral way prevents complications, reduces stress and generates feelings of satisfaction, joy and gratitude in the child and their parents. Objective: to assess the satisfaction of parents of children with special health needs with nursing care. Methodology: quantitative research carried out with 31 parents of children interned in a public pediatric hospital during the month of October 2018. Data were collected using a form and analyzed using descriptive statistics. It should be noted that the study was approved by the Research Ethics Committee under Protocol n. 151/2018. Results: It was found that the level of parental satisfaction is in the regular stratum in relation to the care provided by nurses to children with special health needs. Among the domains analyzed, educational was the one with the highest levels of dissatisfaction, in which none of this item had a median > 4 points. It was also found that participants were dissatisfied with the hospital, which may have reflected in dissatisfaction with the care provided by nurses. Conclusion: Parental satisfaction with nursing care is an important indicator of child care, which can be optimized by providing clear information and guidance, in simple and accessible language, in a respectful, kind and dignified manner.